Inventarisasi Mikroalga dan Protozoa pada Instalansi Pengolahan Air Limbah Karet Sistem Biofilter Skala Laboratorium - Ari Hepi Yanti, Marsi Orina Opat Tri Rima Setyawati (Jurnal Protobiont, 2015)
The treatment of liquid waste from rubber can be done with a biofilter method, which is by using micro-organisms attached to the filter to help the process of organic material degradation. The changes that occur to the organic substance in the waste will affect the composition of microalgae and protozoa during the treatment process. The purposes of this research is to find out types of microalgae and protozoa, their abundance in the rubber waste water treatment plant, and the quality of waste during the treatment. The research was conducted from September 2014 until January 2015. The research was conducted on the laboratory scale through observation of the microalgae and protozoa growth. The findings indicates that there are 36 genera of microalgae and 7 genera of protozoa. It shows that the highest abundance in the group of microalgae belong to Chlorophyceae class, whereas protozoa group is in the Sarcodina class. The genus which is able to adapt well would survive during the waste treatment processing. The genus which survived during wasteÂ  treatment process from the microalgae group was Cyanidium and from the protozoa group was Arcella.